THE IMPORTANCE OF THE ANCHORAGE SYSTEM FOR WORK AT HEIGHT AND RESCUE - dos Santos, Rodrigo Andrade; Montero, José Ivan Caballero (Seven Editora, 2024)
The anchorage system is essential for safety in work at height and rescue operations, playing a crucial role in preventing accidents and protecting the lives of workers. This system consists of a series of components designed to support and distribute loads safely, preventing falls and ensuring stability during activities.The primary function of the anchoring system is to provide a secure attachment point to which personal protective equipment (PPE), such as seat belts and ropes, can be attached. This is vital to prevent falls from heights that can result in serious or even fatal injuries. Proper anchoring allows the worker to move safely, increasing efficiency and confidence while performing their professional activities.In addition, the anchoring system is crucial in rescue operations, where the safety of rescue workers and victims depends on robust and reliable anchoring. In the event of an emergency, it is essential that a well-designed and maintained anchoring system can make the difference between a successful rescue and a disaster.To ensure the effectiveness of the anchoring system, it is essential to follow the determinations of Standard NBR 16325-1 and Standard NBR 16325-2, which deal with Protection Against Falls from Height, in addition to Regulatory Standard NR 18 and Regulatory Standard NR 35. The choice of anchor points must be judicious, considering the load capacity, the resistance of the materials and the suitability for the type of work performed. Regular inspections and maintenance of equipment are equally important to ensure that the system remains in safe operating condition.In this way, the anchorage system is a key piece in the safety of work at height and rescue operations, providing an anchor point and a lifeline that protects workers against falls and increases the effectiveness of rescues. The correct implementation and maintenance of this system are essential to prevent accidents and save lives, underlining the importance of rigorous safety practices in the workplace. DOI:https://doi.org/10.56238/sevened2024.037-065